Desigualdade de gênero no acesso à aposentadoria rural - Castilho, Adriana Guedes de (2024)
This thesis analyzes the right to retirement of the special insured, in the state of Paraíba, between the years 2012 and 2019. Throughout the research, I sought answers about access to the benefit between men and women, through individual semi-structured interviews with female workers and employees of the National Social Security Institute - INSS - and the Federal Court; analysis of administrative processes involving workers who requested a review of the decision that initially denied their retirement request. To this end, I present retrospectives of the relevant legislation and historical facts that are fundamental to understanding the current situation of rural labor rights. From this approach, I was able to conclude that in all the categories analyzed, women have more difficulties retiring, due to the persistence of gender inequality that affects the production of documentary evidence that attests to rural activity. This legislative requirement for access to the benefit brings contradictions with the peasant reality, given that high illiteracy and sexual division of labor with domestic work for women who do not recognize themselves as farmers remain in rural areas. The INSS, by guaranteeing the right to retirement, conceals old forms of power, through bureaucratic and gender domination, worsens the inequality, exclusion and invisibility of female work, which makes it impossible for men and women to access the benefit equally.